Prevalence of Injuries during Brazilian Jiu-Jitsu Training - Alex R. McDonald; Fred A. Murdock; Josh A. McDonald; Christopher J. Wolf (MDPI AG, 2017)
Brazilian jiu-jitsu (BJJ) is a martial art that focuses on groundwork, joint locks, and chokeholds. The purpose of this study is to determine the prevalence of injuries sustained during BJJ training. A 27-question research survey was e-mailed to 166 BJJ gyms in the United States. Demographic information, belt level, weight class, training hours, competition experience, and injury prevalence data were collected. The majority of respondents were Caucasian (n = 96) males (n = 121) with an average age of 30.3 years. Overall, the most common injury locations were to the hand and fingers (n = 70), foot and toes (n = 52), and arm and elbow (n = 51). The most common medically diagnosed conditions were skin infections (n = 38), injuries to the knee (n =26), and foot and toes (n = 19). The most common non-medically diagnosed injuries occurred to the hand and fingers (n = 56), arm and elbow (n = 40), and foot and toes (n = 33). In general, athletes were more likely to sustain distal rather than proximal injuries. Athletes reported more frequent medically diagnosed injuries to the lower extremity and more frequent self-diagnosed injuries to the upper extremity. Upper extremity injuries appear to be more frequent but less severe than lower extremity injuries with the opposite being true for lower extremity injuries.